Environmental Surveillance of Vibrio cholerae O1/O139 in the Five African Great Lakes and Other Major Surface Water Sources in Uganda - Bwire, Godfrey; Debes, Amanda K.; Orach, Christopher G.; Kagirita, Atek; Ram, Malathi; Komakech, Henry; Voeglein, Joseph B.; Buyinza, Ambrose W.; Obala, Tonny; Brooks, W. Abdullah; Sack, David A. (Frontiers in Microbiology, 2018)
Cholera is a major public health problem in the African Great Lakes basin. Two hypotheses might explain this observation namely; the lakes are reservoirs of toxigenic V. cholerae O1 and O139 bacteria or cholera outbreaks are a result of repeated pathogen introduction from the neighboring communities / countries but the lakes facilitate the introductions. A prospective study was conducted in Uganda between February 2015 and January 2016 in which 28 selected surface water sources were tested for the presence of V. cholerae species using cholera rapid test and multiplex PCR. Of 322 water samples tested, 35 (10.8%) were positive for V. cholerae non O1/non O139; 2 samples tested positive for non-toxigenic atypical V. cholerae O139. None of the samples tested had toxigenic V. cholerae O1 or O139 that are responsible for cholera epidemics. Lake Albert region registered the highest number of positive test for V. cholerae non O1/non O139 at 47% (9/19). The peak period for V. cholerae non O1/non O139 positive tests was in March - July 2015 which coincided with the first rainy season in Uganda. This study showed that the surface water sources including the African Great Lakes in Uganda are less likely to be reservoirs for the observed V. cholerae O1 or O139 epidemics though they are natural habitats for V cholerae non O1/non O139 and atypical non-toxigenic V. cholerae O139. Further studies by WGS test of non-toxigenic atypical V. cholerae O139 and physicochemical test of surface water sources that supports V. cholerae should be done to provide more information. Since V. cholerae non O1/non O139 may cause other human infections, their surveillance to understand the potential pathogenicity is needed.